2004
DOI: 10.1111/j.1745-9125.2004.tb00533.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Test of Racial Threat Theory

Abstract: We develop a conceptual model articulating the mechanisms by which racial threat is theorized to affect social control, focusing specifically on the influence of the relative size of the black population on the likelihood that the police will arrest a black citizen suspected of a violent criminal offense. A multilevel analysis of 145, 255 violent crimes reported to police in 182 cities during 2000 shows only qualified support for racial threat theory. Controlling for the amount of race‐specific crime reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 37 publications
9
135
4
Order By: Relevance
“…More recent scholarship also concludes null findings in investigating economic and political threat on Black arrests. Stolzenberg et al [22], for example, find that neither the percentage of Blacks nor the presence of competition in an area is related to an increased probability of Black arrests.…”
Section: 2mentioning
confidence: 99%
“…More recent scholarship also concludes null findings in investigating economic and political threat on Black arrests. Stolzenberg et al [22], for example, find that neither the percentage of Blacks nor the presence of competition in an area is related to an increased probability of Black arrests.…”
Section: 2mentioning
confidence: 99%
“…Racial disparity exists, and the race of the driver impacted the traffic stop decision-making of officers examined in this dissertation. These results are similar to previous studies which found that racial minorities were more likely to be stopped by police compared to Whites (Alpert et al, 2005;Alpert et al, 2007;Engel & Calnon, 2004;Jacobs, 1979;Lundman & Kaufman, 2003;Miller, 2008;Novak, 2004;Novak & Chamlin, 2012;Petrocelli et al, 2003;Rojek et al, 2004;Smith et al, 2006;Stolzenberg et al, 2004;Warren et al, 2006;Withrow, 2004aWithrow, , 2004bWithrow, , 2007. The finding that Black drivers were more likely to be cited is also similar to previous studies (Barnum & Perfetti, 2010;Ingram, 2007;Tillyer & Engel, 2013).…”
Section: All Similarly Situated White and Black Driverssupporting
confidence: 82%
“…Specifically, some studies in criminology and criminal justice have shown that racial minorities are more likely to be stopped by the police than Whites (Alpert, Dunham, & Smith, 2007;Alpert, MacDonald, & Dunham, 2005;Engel & Calnon, 2004;Jacobs, 1979;Lundman & Kaufman, 2003;Miller, 2008;Novak, 2004;Novak & Chamlin, 2012;Petrocelli, Piquero, & Smith, 2003;Rojek, Rosenfeld, & Decker, 2004;Smith, Makarios, & Alpert, 2006;Stolzenberg, D'Alessio, & Eitle, 2004;Warren, Tomaskovic-Devey, Smith, Zingraff, & Mason, 2006;Withrow, 2004a;Withrow 2004b;Withrow, 2007).…”
Section: Racial Bias From Traffic Stop Datamentioning
confidence: 99%
“…Such propositions have been widely tested in relation to pretrial release (Free Jr. 2004;Nagel 1983), sentencing (Bontrager et al 2005;Feldmeyer and Ulmer 2011;Jacobs and Carmichael 2002;Ruddell and Urbina 2004;Stolzenberg et al 2004;Wang 2012;Wang and Mears 2010), the size of police forces (Chamlin 1989;Stults and Baumer 2007), arrest (Chamlin and Liska 1992;Liska and Chamlin 1984;Parker et al 2005) and police use of deadly force (Liska and Yu 1992).…”
Section: Literature Reviewmentioning
confidence: 99%